The IMS-based mobile monitoring system for integrated networks. (1st January 2011) - Lin, Whe Dar; Ke, Chih-Kun; Wu, Mei-Yu; Guo, Ming-Huang
The IP multimedia subsystem (IMS) is able to deliver the multimedia messages through different types of networks, and alleviate the message losing in the single or fixed line network. With IMS supported, many applications can be integrated in the seamless networking environment, so that users can access the network applications anytime and at anywhere. In this paper, we will introduce an on-line monitoring system with IMS platform for integrated networks. The proposal is able to associate with many value-added services, and users can access the services in the easy and convenience way. By the comparisons to other systems, our proposal not only is easily to use and deploy, but also provides most functions.